Teaching Practicums During the Pandemic in an Initial English Teacher Education Program: The Preservice Teachers' Perspective - Verónica Ormeño; Minerva Rosas (Universidad Nacional de Colombia, 2023)
In an initial English teacher education program at a Chilean institution, early and professional practicums were re-invented during the COVID-19 pandemic to ensure the continuity of this process. This study analyzed the context and conditions under which these practicums unfolded and how the process influenced participants' pedagogical and professional knowledge development. Forty-two preservice English language teachers undergoing early and professional practicums online throughout 2020-2021 answered an online questionnaire which was analyzed through descriptive statistics and content analysis. Findings revealed preservice teachers' problems, strengths, weaknesses, and challenges while interacting with pupils, cooperating teachers, and supervisors, as well as the development of some pedagogical and professional knowledge. The findings may serve to make adaptations to increasingly challenging teaching contexts.